Perancangan Data Mining Untuk Analisis Kriteria Nasabah Kredit yang Potensial dan Manfaatnya Untuk Customer Relationship Management Perbankan - Putu Sukma Kurniawan (Journal of Accounting and Investment, 2015)
The presence of data mining problems caused by the explosion of data experienced by many organizations that have accumulated so many years of data (purchasing data, sales data, customer data, transaction data, and others). Examples of industries that use data mining is the banking industry. There are still many banks using conventional methods in the analysis of their customers. This would lead to high operating costs for the bank. The concept of data mining can help banks to get a better analysis of their customers and also help in making the concept of customer relationship management. Data mining can help bank to create profiling customer. Results or final output obtained if the bank can execute customer relationship management is increasing customer loyalty to the bank, increasing profitability, and reducing customer acquisition costs.